Management of Herpes-Associated Erythema Multiforme in a Young Male: A Case Report - Basalamah, Fatimah F.; Dewi, Gremita K.; Ernawati, Diah S.; Fatarnaha, Nisa’a T.; Radithia, Desiana; Ayuningtyas, Nurina F. (e-GiGi, 2025)
Abstract: Erythema multiforme (EM) is an acute mucocutaneous hypersensitivity reaction often triggered by infections or medications. The most common infectious cause is herpes simplex virus (HSV). Herpes-associated erythema multiforme (HAEM) typically presents with sudden, painful oral ulcers and hemorrhagic crusts on the lips. This case report highlights the clinical presentation, diagnosis, and management of a young adult with HAEM. A 20-year-old male presented with multiple painful oral ulcers and lip crusting following a febrile episode. Clinical examination revealed multiple, variably sized ulcers with erythematous borders and yellowish centers. A diagnosis of HAEM was established based on clinical findings and serological tests showing reactive HSV-1 IgG. The patient was hospitalized due to severe pain, dehydration, and inability to eat. Treatment included systemic acyclovir, intravenous fluids, analgesics, and supportive topical therapy with aloe vera extract mouthwash for intraoral lesions and hydrocortisone ointment for lip crusts. The ulcers and pain progressively improved, with complete recovery achieved by the third follow-up visit. This case emphasizes the importance of timely recognition and combined systemic–topical therapy in HAEM. Early antiviral intervention with supportive care can prevent complications, restore nutritional intake, accelerate healing, and improve quality of life. Keywords: herpes-associated erythema multiforme; herpes simplex virus infection; oral ulcer; acyclovir; supportive therapy